Clinical Proteomics in Cancer Research - Lopez, Elena; Madero, Luis; J. Melen, Gustavo; Ramirez, Manuel; H. Roukos, Dimitrios; C. Cho, William (Current Proteomics, 2013)
Clinical proteomics studies are extensively being conducted in recent years. We have outlined some views about proteomics progresses for clinical research, via the understanding the molecular mechanisms of carcinogenesis, tumor response to therapy and biomarker identification versus novel therapeutic target-discovery; as well as proteomerelated methods used in cancer research. Integrative concepts of development of novel therapeutic targets and the application of proteomics in drug development are also discussed. Several aspects are touched including the development of novel therapeutic targets, proteomics as a tool to discover biomarkers, discovery and validation of prognostic and predictive biomarkers, and biobanking versus proteomics. Finally, we envision the application of clinical proteomics for future personalized cancer therapies can set up a consensus that will be reached amongst the scientific community.
Keywords: Cancer